2011
DOI: 10.1080/00221325.2010.533719
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Prosocial Behaviors in Young Children: A Prospective Population-Based Cohort Study

Abstract: Researchers know relatively little about the normative development of children's behaviors aimed at alleviating distress or discomfort in others. In this article, the authors aim to describe the continuity and discontinuity in the degree to which young children in the general population are reported to exhibit specific prosocial behaviors. Data came from the Québec Longitudinal Study of Child Development. Consistent with Hay's model of prosocial development, the results show that there were about as many child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…In fact, a consistent literature suggests that, from early childhood (e.g. Baillargeon et al, 2011;Malti, Gummerum, & Buchmann, 2007) to adolescence and emerging adulthood (e.g. Caprara et al, 2012;Carlo et al, 2015), female displays more prosociality than male.…”
Section: Development Of Prosocialitymentioning
confidence: 99%
“…In fact, a consistent literature suggests that, from early childhood (e.g. Baillargeon et al, 2011;Malti, Gummerum, & Buchmann, 2007) to adolescence and emerging adulthood (e.g. Caprara et al, 2012;Carlo et al, 2015), female displays more prosociality than male.…”
Section: Development Of Prosocialitymentioning
confidence: 99%
“…The results of a longitudinal study conducted by Baillargeon et al (2011) in 2.940 infants found that lack of prosocial behavior was also seen in behavior early childhood. Some children do not want to give or help if there is no regular guidance, which is shown by the child with behaviors, such as not willing to lend his stationery to his friend, does not want to help his friend when he falls, and still exists children who do not want to share the food they have and often fight with each other (Baillargeon et al, 2011). In the development of prosocial behavior that has been carried out in schools, providing an understanding of prosocial behavior in children tends to be done orally by the teacher after the child is seen not showing prosocial behavior and inside learning situation (Jevtic, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining longitudinal trajectories of prosocial behaviour have been few. Yet there is partial support for the developmental framework put forth by Hay (1994) suggesting that prosocial behaviour develops in infancy, becomes more frequent in the second and third years, followed by a decrease around entrance into preschool and formal schooling (fourth to sixth years) (Baillargeon et al, 2011). Hay, Payne & Chadwick (2004) suggested that this decline in prosocial behaviour results from an increased sense of self-interest and social cognition such as understanding that appropriate behavioural responses vary across situations.…”
Section: Introductionmentioning
confidence: 99%